The Metamorphosis. The impact of a young family member's problematic substance use on family life: a meta-ethnography. Issue 1 (31st December 2023) - Lindeman, Sari Kaarina; Lorås, Lennart; Titlestad, Kristine Berg; Bondas, Terese
ABSTRACT: Purpose: This meta-ethnography seeks to provide insight into the impact that a young family member's problematic substance use has on family life. Background: Problematic substance use (PSU) usually emerges in adolescence or young adulthood. Living with a family member with PSU is highly stressful. An understanding is needed of families' experiences and their needs for adapted help and support, hence we have explored the impact of a young family member's PSU on family life. Methods: Systematic literature searches for qualitative research that explores the impact of PSU on family life and family relationships were conducted and the seven stages of meta-ethnography were used. Results: Fifteen articles were included. The Metamorphosis was established as an overarching metaphor. Five main themes accompany this metaphor: stranger in the family; injuring chaos; no trust any more; family lock-up; and helpless societies . Conclusion: The Metamorphosis reflects the all-embracing change experienced by families. Family members have felt powerless and helpless; often they wish to stay involved but do not know how. PSU at a young age can develop into lifelong chronic health challenges. Family-oriented help must be readily available in this phase as parents and siblings become deeply involved. Family involvement is seldom incorporated into routine treatment practices; such incorporation is therefore needed.